Levá»³â€™s Minimax Strategy in Translating a Popular Article: Theory in Practice - Darta, Deta Maria Sri (Journal of Language and Literature, 2015)
Translation is not merely a process of changing meaning from source language into the target one. It stretches far beyond to produce the result. To translate means to communicate; it conveys the message through language. As an act of communication, it touches other areas of disciplines, one of which is culture. Thus, in line with Levá»³â€™s proposal, translation is a decision process. This article would like to explore the process of translating an article taken from popular magazine â€œReaderâ€™s Digest Canadaâ€. It shows the application of Levá»³â€™s minimax strategy in coping with the problem of translating cultural aspect found in the text. The article concludes that some considerations need to be deeply thought before deciding the best way or choice to translate a text into the target language.Keywords: translating culture, minimax strategy, translation shift